REGULATORY AND INSTITUTIONAL FRAMEWORK FOR GENDER PARITY IN PUBLIC ADMINISTRATION OF UKRAINE - Zolotariov V.F.; Bilosorochka S.I. (Pressing Problems of Public Administration, 2017)
The paper explores the active regulatory and institutional framework for the gender parity in Ukraineon its way to European integration. The main directions of their functioning are discussed. Also,analysis has been conducted into the content of the norms of international law and operation of keyinternational organizations, which facilitate the achievement of gender equality in Ukraine.